2008
DOI: 10.1002/dc.20759
|View full text |Cite
|
Sign up to set email alerts
|

Early cytological diagnosis of diffuse malignant mesothelioma of the peritoneum: A case report

Abstract: Mesotheliomas are the most frequent primary malignant tumors of serosal cavities with a poor prognosis. A definitive and early diagnosis on effusion samples is important, because recent advances in therapy for patients with mesothelioma may result in an improved outcome if they are applied to stage I disease. We report a case of malignant peritoneal mesothelioma diagnosed repeatedly by cytology in ascites fluids 1.5 yr before the diagnosis was confirmed by biopsy histology. The cytological diagnoses were suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The only truly useful tool for MM diagnosis at this stage is cytology. 5 The cytological characteristics of MM have been well described. 6,7 Results from laboratories with significant MM experience have reported that the predictive value for a positive MM diagnosis in serous effusions is 100% in their hands.…”
mentioning
confidence: 99%
“…The only truly useful tool for MM diagnosis at this stage is cytology. 5 The cytological characteristics of MM have been well described. 6,7 Results from laboratories with significant MM experience have reported that the predictive value for a positive MM diagnosis in serous effusions is 100% in their hands.…”
mentioning
confidence: 99%
“…Cytological examination of ascitic fluid removed by paracentesis rarely results in a positive finding [8]. According to the data review of previous case reports and the current case of DMPM [9–12], the sensitivity of ascitic fluid cytology in the diagnosis of malignant mesothelioma was 54% (7/13). In clinical practice, ascitic fluid cytology can be used as an initial diagnostic modality for malignant mesothelioma.…”
Section: Discussionmentioning
confidence: 85%
“…Appropriate panel of immunohistochemical (IHC) markers and electron microscopy (EM) are useful in substantiating the diagnosis. [1][2][3] Herein, we present an uncommon case study of a diffuse peritoneal mesothelioma, which was labeled as an adenocarcinoma on ascitic fluid examination and on biopsy, which is based on the presence of ''signet-ring'' cells. Only rarely such cases have been identified.…”
mentioning
confidence: 99%